Laporan kerja persiapan eksperimentasi PKB Anjatan, tanggal 8-21 Maret, 1976 - Sutaryat T. (Pusat Inotek Pendidikan, Badan Penelitian & Pengembangan Pendidikan & Kebudayaan, Departemen Pendidikan & Kebudayaan, 1976)
Working report on the preparation of the development of a non-formal education centre in Anjatan Subdistrict, Indramayu Regency, West Java.